Coprecipitation Preparation of Cu/Zn/Al-Hydrotalcite-Like Compound for Copper Removal from Electroplating Wastewater - Dekui Bai; Xiaofang Wang; Dongxia Huo; Quanhong Ying; Ni Wang; Baixue Xia (Journal of Chemistry)
Cu/Zn/Al-hydrotalcite-like compound (Cu/Zn/Al-HTlc) was prepared by the coprecipitation method with ZnII, AlIII cations solution, and electroplating wastewater containing CuII cation. The preparation conditions of Cu/Zn/Al-HTlc were optimized. The metal ion pollutants removal effect and iodide maximum adsorption capacity of Cu/Zn/Al-HTlc were also studied. The physicochemical properties of the Cu/Zn/Al-HTlc were analyzed by X-ray diffraction, FTIR, SEM, N2 adsorption-desorption isotherms, and TG-DTG. The results showed that Cu/Zn/Al-HTlc should be prepared with the ZnII-AlIII molar ratio of 1.5 : 1, pH = 11, and aged at room temperature for 0.5 d. Structural analysis showed that the Cu/Zn/Al-HTlc was a layered compound. CuII and other metal ion pollutants can also be successfully removed from electroplating wastewater in the preparation process of Cu/Zn/Al-HTlc and reached Chinese National Emission Standard (GB 21900-2008). The optimal adsorption condition of calcinated Cu/Zn/Al-HTlc for iodide was as follows: the solid-liquid ratio was 1 : 250, the pH value was 8, and the adsorption process was carried out at 25°C for 30 min. The saturated adsorption capacity reached 1000 mg·g−1 at the optimal adsorption condition. The main reason for this high-saturated adsorption capacity of Cu/Zn/Al-HTlc was that iodide penetrated into the layered structure of Cu/Zn/Al-HTlc by physical adsorption and CuII undergoes a specific redox reaction, producing CuI. Hence, coprecipitation synthetic technology and prepared Cu/Zn/Al-HTlc could be potentially used for electroplating wastewater treatment.